A dimensionless parametric study on the performance of a single-effect solar still (Research, Society and Development, 2021)
Research on the design and operation of solar stills is relatively advanced, but many works have focused only on the description of the individual behavior and operation of experimental apparatus that can be operated under specific experimental or natural conditions. In any case, optimization of the systems requires the correlation of several parameters by means of mathematical modeling, which can be relatively complex. In this work, appropriate global normalization of governing mathematical equations employing dimensionless numbers has been successfully applied for the versatile operation of solar stills. In this novel approach, optimized conditions to design efficient solar stills are presented and discussed. The results also indicated that the generalized dimensionless model could be able of predicting the still performance. The reasons and processes behind the changing trends of the results depend on the simple analysis of the corresponding nondimensional number.